Предмет: Алгебра,
автор: milanagregoreva12
2•(-3)•(-7)-3•(-3)+2•(-7)
Ответы
Автор ответа:
0
Ответ:
2•(-3)•(-7)-3•(-3)+2•(-7) = 42 + 9 - 14 = 51 - 14 = 37
Автор ответа:
0
Ответ:37
Объяснение:
2•(-3)•(-7)-3•(-3)+2•(-7)
2*(-3)*(-7) = 42
-3*(-3) = 9
2*(-7)=14
42+9-14=37
37
mrcotek:
я по действиям сделал (для 5-6 класса)
Похожие вопросы
Предмет: Алгебра,
автор: grepvik
Предмет: Геометрия,
автор: danil5599
Предмет: Математика,
автор: skripnikulia47
Предмет: Математика,
автор: pihpoh24
Предмет: Математика,
автор: belogubova2004